2021
DOI: 10.3390/en14248415
|View full text |Cite
|
Sign up to set email alerts
|

The Contributions of Biomass Supply for Bioenergy in the Post-COVID-19 Recovery

Abstract: This research investigates how biomass supply chains (BSChs) for bioenergy within the broader bioeconomy could contribute to the post-COVID-19 recovery in three dimensions: boosting economic growth, creating jobs, and building more resilient and cleaner energy systems in four future scenarios, in the short term (by 2023) and long term (by 2030). A SWOT analysis on BSChs was used for generating a questionnaire for foresight by a two-round Delphi study. To interpret the results properly, a short survey and liter… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(10 citation statements)
references
References 49 publications
0
10
0
Order By: Relevance
“…The authors reported early issues associated with labour availability, but found the wood pellet industry to be resilient, with increased production levels over the course of the pandemic, likely due to stable demand driven by long-term contracts. Similarly, Kulisic et al [10] observed few changes within the global bioeconomy as a result of the pandemic. The authors noted early issues related to transportation logistics and labour; however, the bio-based industries generally adapted quickly, suggesting an inherent resilience to shocks.…”
Section: Discussionmentioning
confidence: 91%
See 2 more Smart Citations
“…The authors reported early issues associated with labour availability, but found the wood pellet industry to be resilient, with increased production levels over the course of the pandemic, likely due to stable demand driven by long-term contracts. Similarly, Kulisic et al [10] observed few changes within the global bioeconomy as a result of the pandemic. The authors noted early issues related to transportation logistics and labour; however, the bio-based industries generally adapted quickly, suggesting an inherent resilience to shocks.…”
Section: Discussionmentioning
confidence: 91%
“…Bioenergy, including wood pellets, is expected to play a crucial role in net-zero and energy transition plans around the globe [31] and can also make a meaningful contribution in the post COVID-19 economic recovery [10]. Given the rising importance of wood pellets as a renewable fuel, it is useful to understand how the sector responds to disturbances and identify opportunities to improve resilience to future shocks [6].…”
Section: The Canadian Wood Pellet Industry and Its Integration Within...mentioning
confidence: 99%
See 1 more Smart Citation
“…The results of the comparative econometric analysis of global price trends between the energy from fossil fuels and their renewable alternatives suggest that the latter are less susceptible to external shocks (such as COVID) and therefore improve the stability of the economic system. Kulišić et al [5] further investigate how biomass supply for bioenergy could contribute to the post-COVID recovery in three dimensions: boosting economic growth, creating jobs, and building more resilient and cleaner energy systems. The results of an extensive qualitative analysis suggest that the paramount impact of a stronger mobilization of biomass supply chains would be on economic growth, followed by a contribution to the resilient and cleaner energy systems, and job creation.…”
Section: Economic Feasibility Contribution Of Bioeconomy To Post-covi...mentioning
confidence: 99%
“…They reveal pathways and challenges associated with this transition. The first group of papers [4][5][6] is assessing the potentials and relative significance of bioeconomy in the post-COVID economic recovery. This is followed by a group of four papers [7][8][9][10] that are assessing technical or economic feasibility of knowledge-intensive biobased applications at the industrial, or regional, scale.…”
Section: Introductionmentioning
confidence: 99%